Iron Deficiency Anemia: Focus on Infectious Diseases in Lesser Developed Countries - Julia G. Shaw; Jennifer F. Friedman (Anemia)
Iron deficiency anemia is thought to affect the health of more than one billion people worldwide, with the greatest burden of disease experienced in lesser developed countries, particularly women of reproductive age and children. This greater disease burden is due to both nutritional and infectious etiologies. Individuals in lesser developed countries have diets that are much lower in iron, less access to multivitamins for young children and pregnant women, and increased rates of fertility which increase demands for iron through the life course. Infectious diseases, particularly parasitic diseases, also lead to both extracorporeal iron loss and anemia of inflammation, which decreases bioavailability of iron to host tissues. This paper will address the unique etiologies and consequences of both iron deficiency anemia and the alterations in iron absorption and distribution seen in the context of anemia of inflammation. Implications for diagnosis and treatment in this unique context will also be discussed.